2014
DOI: 10.1002/app.40942
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polyhydroxylated polybutadiene binding 2,2′‐thiobis(4‐methyl‐6‐tert‐butylphenol) with isophorone diisocyanate

Abstract: A macromolecular hindered phenol antioxidant, polyhydroxylated polybutadiene containing thioether binding 2,2′‐thiobis(4‐methyl‐6‐tert‐butylphenol) (PHPBT‐b‐TPH), was synthesized via a two‐step nucleophilic addition reaction using isophorone diisocyanate (IPDI) as linkage. First, the OH groups of PHPBT reacted with secondary NCO groups of IPDI to form the adduct PHPBT‐NCO, then the PHPBT‐b‐TPH was obtained by one phenolic OH of 2,2′‐thiobis(4‐methyl‐6‐tert‐butylphenol) (TPH) reacting with the PHPBT‐NCO. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In our work, a novel macromolecular hindered phenol antioxidant, polyhydroxylated polybutadiene containing thioether binding 2,2 0 -thiobis(4-methyl-6-tert-butylphenol) (PHPBT-b-TPH), as shown in Figure 1, was successfully synthesized by the combination of a thiol-ene click reaction and a two-step nucleophilic addition reaction. 24,36 We found that the PHPBT-b-TPH exhibited excellent extraction resistance in NR matrix and revealed that the reasons for the excellent extraction resistance are mainly attributed to its higher molecular weight and better compatibility with NR than that of TPH. Additionally, the co-vulcanization between PHPBT-b-TPH and NR matrix was also the important factor for the improvement of extraction resistance.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In our work, a novel macromolecular hindered phenol antioxidant, polyhydroxylated polybutadiene containing thioether binding 2,2 0 -thiobis(4-methyl-6-tert-butylphenol) (PHPBT-b-TPH), as shown in Figure 1, was successfully synthesized by the combination of a thiol-ene click reaction and a two-step nucleophilic addition reaction. 24,36 We found that the PHPBT-b-TPH exhibited excellent extraction resistance in NR matrix and revealed that the reasons for the excellent extraction resistance are mainly attributed to its higher molecular weight and better compatibility with NR than that of TPH. Additionally, the co-vulcanization between PHPBT-b-TPH and NR matrix was also the important factor for the improvement of extraction resistance.…”
Section: Introductionmentioning
confidence: 89%
“…Polyhydroxylated polybutadiene containing thioether (PHPBT) 37 and PHPBT-b-TPH 36 were obtained according to our reported method, as shown in Figure 1. Hydroxyl-terminated polybutadiene (HTPB, Figure 1) and polybutadiene (PB, under the trademark Ricon 157) were supplied by Cray Valley Co., USA.…”
Section: Methodsmentioning
confidence: 99%
“…Polyhydroxylated polybutadiene containing thioether binding 2,2′‐thiobis (4‐methyl‐6‐ tert ‐butylphenol) (PHPBT‐ b ‐TPH) was synthesized in our lab . 2,2′‐Thiobis (4‐methyl‐6‐ tert ‐butylphenol) (TPH) was supplied by Zibo Debaiyi Industral & Trading Co. Ltd., China.…”
Section: Methodsmentioning
confidence: 99%
“…In order to minimize such drawbacks, increasing the molecular weight of hindered phenols by functionalization of polymer has attracted much attention in recent years . The polymer include natural rubber, polyolefin, polybutadiene, and others . Podesva et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation